Search for global order: the problems of survival - d'Orville, Hans ed. (InterAction Council New YorkUS, 1993)
Contains an account of the sequence of debates on how the global challenges of population explosion, development and poverty, environmental degradation, global warming, mass migrations and arms proliferation could be tackled in the world community.